History of whaling in Annobón, Equatorial Guinea, and new evidence of its continued occurrence - Fielding, Russell; Barrientos, Christian (J. Cetacean Res. Manage., 2021)
A regular, though infrequent, artisanal whaling operation targeting humpback whales has been known to occur from the West African island of Annobón, Equatorial Guinea, since the late 18th century. Little has been known outside of Equatorial Guinea about this whaling operation since the mid-1970s. This paper presents a brief history of Annobonés whaling, describes recently surfaced evidence of its continuation as recently as 2017 and considers the future of the operation.